Why administrative reforms in international organizations fall short? The case of UNAIDS / Oliver Nay - Oliver, Nay (2010)
This paper focuses on administrative reforms launched within the UN system. It is based on an empirical analysis of the UNAIDS Programme, an interorganizational system bringing together ten UN agencies to combat the HIV/AIDS epidemic, with the support of a Secretariat. Firstly, the paper pays attention to UN system-wide reform as an institutional context that created a momentum for reforming UNAIDS. Secondly, it explores the conditions under which the reform of UNAIDS has been implemented since the early 2000s. Thirdly, it examines some of the side effects of the reform, with particular emphasis on competition between UN agencies, organizational complexity, and bureaucratization. The conclusion argues that multilateral agencies have turned their primary attention to management challenges in the 2000s, but reformers have not proved to be able to anticipate and control the various effects of the change they have initiated